Canagliflozin alleviates acetaminophen-induced renal and hepatic injury in mice by modulating the p-GSK3β/Fyn-kinase/Nrf-2 and p-AMPK-α/STAT-3/SOCS-3 pathways - Abeer Bishr; Bassant M. El-Mokadem; Asmaa A. Gomaa (Scientific Reports)
Abstract Despite the fact that canagliflozin (Cana), a sodium-glucose cotransporter 2 inhibitor, is an anti-diabetic medication with additional effects on the kidney, there is limited experimental data to deliberate its hepato-reno-protective potentiality. Acetaminophen (APAP) overdose remains one of the prominent contributors to hepato-renal damage. Aim: Our study assessed the novel effect of Cana against APAP-induced toxicities. Main methods: mice were randomized into five groups: negative control, Cana25, APAP, Cana10 + APAP, and Cana25 + APAP. Cana was given for 5 days; a single dose of APAP was injected on the 6th day, followed by the scarification of animals 24 h later. Key findings: Pre-treatment with Cana ameliorated hepatic and renal functions, whereas, on the molecular levels, Cana promoted hepatic/renal P-AMP-activated protein kinase-α/ protein kinase B (p-Akt)/Glycogen synthase kinase (p-GSK3β) protein expression. Alternatively, Cana dampened the expression of STAT-3 and Fyn-kinase genes with a subsequent increase in the contents of suppressor of cytokine signaling (SOCS)-3 and also boosted the contents of the nuclear factor erythroid related factor 2 (Nrf-2)/heme oxygenase (HO)-1/ NADPH quinone oxidoreductase (NQO)-1 axis. The crosstalk between these paths ameliorated the APAP-induced hepatorenal structural alterations. Significance: Cana hepatorenal protective impact was provoked partly through modulating p-AMPK-α /SOCS-3/STAT-3 and GSK3β/Fyn-kinase signaling for its anti-inflammatory and antioxidant effects.